2012
DOI: 10.1242/jcs.116442
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the angulin family consisting of LSR, ILDR1 and ILDR2: tricellulin recruitment, epithelial barrier function and implication in deafness pathogenesis

Abstract: SummaryTricellular tight junctions (tTJs) seal the extracellular space at tricellular contacts (TCs), where the corners of three epithelial cells meet. To date, the transmembrane proteins tricellulin and lipolysis-stimulated lipoprotein receptor (LSR) are known to be molecular components of tTJs. LSR recruits tricellulin to tTJs, and both proteins are required for the full barrier function of epithelial cellular sheets. In the present study, we show that two LSR-related proteins, immunoglobulin-like domain-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
227
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(241 citation statements)
references
References 38 publications
11
227
1
Order By: Relevance
“…Two types of integral membrane proteins, tricellulin (Ikenouchi et al, 2005) and angulin family proteins, which include angulin-1/LSR, angulin-2/ILDR1, and angulin-3/ILDR2 (Higashi et al, 2013;Masuda et al, 2011), have been identified as specific molecular components of tTJs. Tricellulin is a member of the TAMP family containing occludin with four transmembrane domains (Ikenouchi et al, 2005;Raleigh et al, 2010;Steed et al, 2009), while angulins are singlepass membrane proteins with an Ig-like domain (Masuda et al, 2011;Higashi et al, 2013). Notably, angulins recruit tricellulin to TCs and at least one of the angulin family members is expressed in each epithelium with tricellulin (Higashi et al, 2013;Masuda et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two types of integral membrane proteins, tricellulin (Ikenouchi et al, 2005) and angulin family proteins, which include angulin-1/LSR, angulin-2/ILDR1, and angulin-3/ILDR2 (Higashi et al, 2013;Masuda et al, 2011), have been identified as specific molecular components of tTJs. Tricellulin is a member of the TAMP family containing occludin with four transmembrane domains (Ikenouchi et al, 2005;Raleigh et al, 2010;Steed et al, 2009), while angulins are singlepass membrane proteins with an Ig-like domain (Masuda et al, 2011;Higashi et al, 2013). Notably, angulins recruit tricellulin to TCs and at least one of the angulin family members is expressed in each epithelium with tricellulin (Higashi et al, 2013;Masuda et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Tricellulin is a member of the TAMP family containing occludin with four transmembrane domains (Ikenouchi et al, 2005;Raleigh et al, 2010;Steed et al, 2009), while angulins are singlepass membrane proteins with an Ig-like domain (Masuda et al, 2011;Higashi et al, 2013). Notably, angulins recruit tricellulin to TCs and at least one of the angulin family members is expressed in each epithelium with tricellulin (Higashi et al, 2013;Masuda et al, 2011). shRNA-mediated depletion of tricellulin or angulin-1/LSR in cultured epithelial cells revealed that these molecules are required for normal tTJ formation as well as the full barrier function of epithelial cellular sheets (Higashi et al, 2013;Ikenouchi et al, 2005;Masuda et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tricellulin is expressed in the inner ear, and mutations in this gene have been linked to DFNB49 (48), suggesting that the pathogenesis of this impairment may involve aberrations in LSR-promoted tricellular tight junction formation, which require proper targeting of tricellulin. Similar to LSR, it now appears that ILDR is also involved in targeting of tricellulin to the tight junctions in the inner ear and elsewhere in the body (49). There is a growing body of evidence to suggest that the lipoprotein receptors possess multiligand, multifunctional capabilities (50).…”
Section: Figurementioning
confidence: 99%
“…The tricellular tight junction (tTJ) is a specialized cell junction different in ultrastructure from that of the bTJ (5). Unlike the bTJ, which is made of claudin and occludin (6), the proteins making the tTJ include tricellulin and angulins (LSR/angulin-1, ILDR1/angulin-2, and ILDR2/angulin-3) (7,8). Transgenic knockout (KO) of either tricellulin or Ildr1 in mice causes hearing loss due to degeneration of mechanosensory cochlear hair cells in the organ of Corti (9, 10).…”
mentioning
confidence: 99%